2001
DOI: 10.1007/s002840010310
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization of Mercury by Immobilized Bacteria (Klebsiella pneumoniae) in Different Support by Using Fluidized Bed Bioreactor

Abstract: Klebsiella pneumoniae, a mercury-resistant bacterial strain able to reduce ionic mercury to metallic mercury, was isolated from wastewater of Casablanca. This strain exhibits high minimal inhibition concentrations for heavy metals such as mercury 2400 microM, lead 8000 microM, silver 2400 microM, and cadmium 1000 microM. This bacterium was immobilized in alginate, polyacrylamide, vermiculite, and cooper beech and was used for removing mercury from a synthetic water polluted by mercury by using a fluidized bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Roane et al 38) reported that R. eutropha JMP134, a 2,4-D degrader which was sensitive to Cd, could degrade 2,4-dichlorophenoxyacetic acid even in the presence of Cd when it was grown in a consortium with Cd-detoxifying bacteria. Zeroual et al 48) observed that a strain of Klebsiella pneumoniae could tolerate 2400 µM of mercury and 1000 µM of cadmium. The resting cells of P. aeruginosa PU21 (Rip64) have been reported to take up upto 110 mg Pb/g dry cell mass whereas, the inactivated cells could absorb 70 mg Pb/g dry cell 12) .…”
Section: Discussionmentioning
confidence: 99%
“…Roane et al 38) reported that R. eutropha JMP134, a 2,4-D degrader which was sensitive to Cd, could degrade 2,4-dichlorophenoxyacetic acid even in the presence of Cd when it was grown in a consortium with Cd-detoxifying bacteria. Zeroual et al 48) observed that a strain of Klebsiella pneumoniae could tolerate 2400 µM of mercury and 1000 µM of cadmium. The resting cells of P. aeruginosa PU21 (Rip64) have been reported to take up upto 110 mg Pb/g dry cell mass whereas, the inactivated cells could absorb 70 mg Pb/g dry cell 12) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported improvements in metal removal by immobilization of protozoa, yeast or bacterial cells (Zeroual et al 2001). Bacteria and yeast communities are central to the functioning of terrestrial ecosystem and consist of a large number of different bacterial and yeast type (O-Muter et al 2002;Boenigk and Arndt 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Most dyes have long been considered nonbiodegradable or nontransformable under aerobic conditions [35]. Zeroual et al (2001) [49] used bacterial strain Enterobacter agglomerans on different support materials by using fluidized bed reactor (FBR) and found that the bacteria had high effectiveness of decolorization of water polluted with azo dye methyl red. The immobilized cells of E. agglomerans exhibited higher capability for the complete decolorization of methyl red (100 mg/L) after 6 h of incubation under aerobic condition.…”
Section: Immobilized Bacteria Under Aerobic Conditionmentioning
confidence: 99%
“…Immobilization of microorganism has been reported useful in biological wastewater treatment [47][48][49][50]. There are various methods of immobilization of bacterial cells.…”
Section: Immobilized Bacteriamentioning
confidence: 99%